The consequences of diverse empathic responses in nurse-patient interactions: a discourse analysis. (3rd April 2018) - Crawford, Tonia; Roger, Peter; Candlin, Sally
ABSTRACT: Background: Empathy in healthcare interactions has been a focus of considerable research since the 1980s, and discourse analysis has been used more recently to identify how empathy is accomplished in interactions between healthcare professionals and their patients. However, there has been little research using naturally occurring nurse/patient interactions. Method: This study employs discourse analysis from an interactional sociolinguistic approach to examine and describe the interactional consequences of empathy during nurse-patient interactions. Results: The consequence of the display of empathy was an extended interaction with numerous affiliative responses by both parties, showing evidence of good rapport and a therapeutic relationship. This is compared to interactions where minimal affiliative responses are evident. The exchange with the patient is cut short with a quick return to the clinical agenda after a momentary acknowledgement of the patient's concern. Where empathy is not displayed, the patient does not elaborate on concerns, thereby limiting the development of rapport and trust. The display of empathy has been linked to patient satisfaction and improved patient outcomes. Conclusion: Examining natural nurse-patient interactions allows for a greater understanding of the consequences of various communicative approaches and levels of engagement. This awareness can enable the development of stronger communicative competence of health professionals, enhancing professional practice and patient satisfaction.